Fomesafen Programs for Palmer Amaranth (Amaranthus palmeri) Control in Sweetpotato. (June 2016) - Barkley, Susan L.; Chaudhari, Sushila; Jennings, Katherine M.; Schultheis, Jonathan R.; Meyers, Stephen L.; Monks, David W.
Abstract : Studies were conducted in 2012 and 2013 to determine the effect of fomesafen based Palmer amaranth control program in 'Covington' and 'Evangeline' sweetpotato cultivars. Treatments consisted of fomesafen pretransplant alone at 0.20, 0.28, 0.36, 0.42, 0.56, and 0.84 kg ai ha −1 or followed by (fb) S -metolachlor at 1.12 kg ai ha −1 0 to 7 d after transplanting (DAP), fomesafen at 0.28 kg ha −1 fb S -metolachlor at 1.12 kg ha −1 14 DAP, flumioxazin pretransplant at 0.105 kg ai ha −1, S -metolachlor at 1.12 kg ha −1 0 to 7 DAP, clomazone at 0.63 kg ha −1 0 to 7 DAP, napropamide at 2.24 kg ha −1 0 to7 DAP, flumioxazin fb S -metolachlor 0 to 7 DAP, and flumioxazin fb clomazone fb S -metolachlor 14 DAP. Fomesafen pretransplant at 0.28 to 0.84 kg ha −1 alone or followed by S -metolachlor at 1.12 kg ha −1 0 to 7 DAP provided 80 to 100% Palmer amaranth control without reduction of yield and significant (< 13%) injury in Covington and Evangeline sweetpotato. Flumioxazin alone or fb S -metolachlor and flumioxazin fb clomazone fb S -metolachlor provided Palmer amaranth control (≥ 95%) with little injury (≤ 5%) and similar yield to the weed-free check. Clomazone alone did not cause injury, but controlled only 24 to 32% of Palmer amaranth at 50 DAP, which resulted in reduced no. 1, marketable, and total sweetpotato yield. Napropamide provided inconsistent control of Palmer amaranth in both years; therefore jumbo and total sweetpotato yield was reduced as compared to the weed-free check in 2012. Palmer amaranth control, sweetpotato cultivar tolerance, and yield in treatments with fomesafen fb S -metolachlor were similar to flumioxazin fb S -metolachlor. In conclusion, a herbicide program consisting of pretransplant fomesafen (0.28 to 0.42 kg ha −1 ) fb S -metolachlor (1.12 kg ha −1 ) is a potential option to control Palmer amaranth without causing significant injury and yield reduction in sweetpotato.